Evolution of operator business models in the future Internet of Things - Sassali, Pertti (2017)
The Internet of Things is a paradigm or vision, where virtually any object can be connected to Internet, enabling new smart services to people and businesses. Mobile network operators have entered the aspiring market, but because of the novelty of the paradigm, many aspects of business and technology in the area are still undiscovered. In this thesis, views of possible mobile network operator business models were presented, and the object was to discover, how mobile network operator business models change in the future Internet of Things. The research based on theoretical concepts of value, innovation diffusion and technology adoption life cycle, as well as business models, corporate strategy and enabling technologies constituting Machine-to-Machine communications and the future Internet of Things. The qualitative research method used in this thesis was based on Mika Mannermaa’s evolutionary futures research, and it was applied to concepts of business model evolution and innovation life cycle models. Theoretical basis of the research was presented using literature, and the methodological framework was constructed using both life cycle models and system methodologies. Main findings of this research indicated, that a mobile network operator’s business models change as the diffusion of innovation, the Internet of Things, continues. Several key elements of the business model evolve, as technology is adopted more and the surrounding ecosystem grows creating more actors and relationships between them. A guideline for mobile network operators was proposed to support the business in the future Internet of Things In the end, research and results were reviewed and future research objectives were found, especially regarding middleware platforms and information security.